Spectra of coherent bremsstrahlung and radiation formed by 0.8 GeV electrons moving near the axis and plane of diamond crystal - Ganenko, V.B.; Zhebrovskij, Yu.V.; Kolesnikov, L.Ya.; Rubashkin, A.L. (Вопросы атомной науки и техники, 2000)
Spectra of coherent bremsstrahlung and radiation spectra of the electron moving near the axis and plane of diamond crystal have been measured using the electron beam of low intensity with 0.8 GeV energy. Experimental data are compared with calculations based on the coherent bremsstrahlung theory.